Effects of bamboo density and chemical properties on the properties of particleboard produced from Giganfochloa Scortechinii / Jamaludin Kasim and Abd. Jalil Hj. Ahmad - Kasim, Jamaludin; Hj. Ahmad, Abd. Jalil (Universiti Teknologi MARA Cawangan Pahang, 2005)
Density and chemical properties of 1 -, 2- and 3-y-old Gigantochloa scortechinii were determined and their effects on the particleboard properties were investigated by means of correlation analysis. Predictive equations of the board variables viz; age, particle size, resin and wax content on the board properties were also derived by regression analysis. From the study, density was found to increase with bamboo age and culm portion. Only the chemical properties of cold water, hot water and alkali soluble were significantly affected by increased age and culm height. Holocellulose on the other hand only showed an increasing trend with age. Bamboo density only affected the modulus of elasticity of the particleboard. The chemical properties of cold, hot water soluble, ash and holocellulose content showed positive correlation with screw withdrawal (edge). The physical properties of f -hr and 24-hrs thickness swelling were negatively correlated with the chemical properties of cold, hot water, alkali solubles and holocellulose content. All the regression equations derived in the study were found to be significant at p < 0.05 with correlation of determination (R2) of over 50%. The equations could be used as a primary device to predict the properties of particleboard produced from other sources manufactured under the same conditions used in this study.